FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PAKET WISATA KE TAMAN NASIONAL GUNUNG MERBABU – JAWA TENGAH - Meylani Tuti; Al Agus Kristiadi; Devi Nurhasanah (Eduturisma, 2018)
This study aims to determine the factors that influence decision making partially and simultaneously influence the decision to visit Mount Merbabu National Park. The population in this study is visitors in the Mount Merbabu National Park, with the sample used in this study as many as 90 people. The sampling technique used is accidental sampling. Data analysis method used in this research is validity test, reliability test, classic assumption test (normality test, multicollinearity test, heteroscedasticity test and linearity test). While hypothesis testing includes F test, t test and partial correlation analysis and coefficient of determination (R²). From the results of the analysis it can be seen that Tourist Characteristics (X1), Travel Benefits (X2), Travel Descriptions (X3) and Tourism Destination Areas (X4) have an influence on Visiting Decisions (Y) both partially and simultaneously.